Factors that influencing organizational commitment in X Islamic Education Foundation - Aulia, Nurul; Kho, Ardi (Institute of Computer Science (IOCS), 2024)
Educators and teaching staff are the human resources in schools. Quality resources will have a positive impact on organizational success. Commitment from educators and teaching staff is needed to create a supportive and motivated work environment. The high turnover rate at the Yayasan Pendidikan Islam X Tangerang is the reason this research was conducted to analyze the commitment of educators and staff. There are many factors that influence commitment, some of which are leadership style, job involvement, and perceived organizational support. Job satisfaction acts as a mediator in testing the effect of these factors on organizational commitment. This research was conducted at Yayasan Pendidikan Islam X Tangerang to the entire population of 38 people. The cross-sectional method was used in quantitative research by distributing online questionnaires. This research used the PLS-SEM analysis method. The results of this study state that there is a positive influence between school leadership style, job involvement, and perceived organizational support on organizational commitment. Job satisfaction also mediates the relationship between school leadership style and job involvement on organizational commitment.